1162. Epidemiology of Carbapenem-Resistant Pseudomonas aeruginosa Identified Through the Emerging Infections Program (EIP), United States, 2016–2017. (26th November 2018) - Grass, Julian; Bulens, Sandra; Bamberg, Wendy; Janelle, Sarah J; Stendel, Patrick; Jacob, Jesse T; Bower, Chris; Sukumaran, Stephen; Wilson, Lucy E; Vaeth, Elisabeth; Li, Linda; Lynfield, Ruth; et al.
Abstract: Background: Pseudomonas aeruginosa is intrinsically resistant to many commonly used antimicrobials and carbapenems are often required to treat infections. We describe the epidemiology and crude incidence of carbapenem-resistant P. aeruginosa (CRPA) in the EIP catchment area. Methods: From August 1, 2016 through July 31, 2017, we conducted laboratory- and population-based surveillance for CRPA in selected metropolitan areas in Colorado, Georgia, Maryland, Minnesota, New Mexico, New York, Oregon, and Tennessee. We defined an incident case as the first isolate of P. aeruginosa -resistant to imipenem, meropenem, or doripenem from the lower respiratory tract, urine, wounds, or normally sterile sites identified from a resident of the EIP catchment area in a 30-day period. Patient charts were reviewed. A random sample of isolates was screened at CDC for carbapenemases using the modified carbapenem inactivation method (mCIM) and real-time PCR. Results: During the 12-month period, we identified 3, 042 incident cases among 2, 154 patients. The crude incidence rate was 21.2 (95% CI, 20.4–21.9) per 100, 000 persons and varied by site (range: 7.7 in Oregon to 31.1 in Maryland). The median age of patients was 64 years (range: <1–101) and 41.2% were female. Nearly all (97.1%) had at least one underlying condition and 10.2% had cystic fibrosis (CF); 17.8% of cases were from CF patients. For most cases, isolates were from the lower respiratory tract (49.2%) or urine (35.3%) and occurred in patients with recent hospitalization (87.2%) or indwelling devices (70.3%); 8.7% died. At the clinical laboratory, 84.7% of isolates were susceptible to an aminoglycoside and 66.4% to ceftazidime or cefepime. Among the 391 isolates tested, nine (2.3%) were mCIM-positive; one had a carbapenemase detected by PCR ( bla VIM-4 ). Conclusion: The burden of CRPA varied by EIP site. Most cases occurred in persons with healthcare exposures and underlying conditions. The majority of isolates were susceptible to at least one first-line antimicrobial. Carbapenemase producers were rare; a more specific phenotypic definition would greatly facilitate surveillance for these isolates. Disclosures: All authors: No reported disclosures.